2005
DOI: 10.1021/ie0499409
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer in a Rotating Packed Bed with Viscous Newtonian and Non-Newtonian Fluids

Abstract: A theoretical analysis was developed to predict the apparent viscosity of a non-Newtonian fluid in a rotating packed bed. It is based on laminar liquid film flow on a rotating disk with the assumption of the randomly inclined surfaces in the rotating packed bed. In addition, experiments of deoxygenation were performed in glycerol solutions and CMC solutions, which are Newtonian and shear-thinning fluids, respectively. It is shown that mass transfer coefficients decreased with increasing viscosity, while the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 16 publications
1
57
0
Order By: Relevance
“…Eldabe et al [10] studied the thermal-diffusion and diffusion-thermo effects on mixed free-forced convection and mass transfer boundary layer flow for non-Newtonian fluid with temperature dependent viscosity by the aid of Chebyshev finite difference method. Later, Chen et al [11] developed a theoretical analysis to predict the apparent viscosity of laminar non-Newtonian liquid film in a rotating packed bed. It was shown that mass transfer coefficients decreased with increasing viscosity, while the centrifugal force still revealed effective in enhancing mass transfer in viscous media.…”
Section: Introductionmentioning
confidence: 99%
“…Eldabe et al [10] studied the thermal-diffusion and diffusion-thermo effects on mixed free-forced convection and mass transfer boundary layer flow for non-Newtonian fluid with temperature dependent viscosity by the aid of Chebyshev finite difference method. Later, Chen et al [11] developed a theoretical analysis to predict the apparent viscosity of laminar non-Newtonian liquid film in a rotating packed bed. It was shown that mass transfer coefficients decreased with increasing viscosity, while the centrifugal force still revealed effective in enhancing mass transfer in viscous media.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the gas-liquid mass transfer would frequently be enhanced by a factor of 10-100 and the dramatic reduction in the equipment volume would be achieved, thereby reducing the capital and operating costs [5]. A variety of studies have appeared in which the attention was focused on the applications of the countercurrent-flow RPB in diverse processes such as distillation [6][7][8][9][10][11], absorption [12][13][14][15][16][17][18][19][20][21][22][23][24][25], stripping [26][27][28][29][30], deaeration [31][32][33][34][35], reactive precipitation [36][37][38][39][40][41][42][43][44][45][46][47], and ozone oxidation [48][49][50][51]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the size of the RPB would be dramatically reduced and, thus, the capital and operating costs would be reduced simultaneously [5]. The RPB can be used to enhance the O 3 transfer from gas phase to liquid phase based on the studies, which presented that the RPB has a wide applicability in a variety of gas-liquid contacting processes such as distillation [6,7], absorption [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], stripping [24][25][26][27], deaeration [28][29][30][31][32], reactive precipitation [33], and ozone oxidation [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%